Self-esteem moderates the influence of self-presentation style on Facebook users' sense of subjective well-being. (August 2018) - Jang, Wonseok (Eric); Bucy, Erik P.; Cho, Janice
Abstract: This study examines the extent to which self-esteem moderates the influence of self-presentation style (true self versus strategic self) on Facebook users' subjective well-being, including measures of self-reported happiness and subjective vitality. To investigate this relationship, we conducted two experimental tests involving actual Facebook users recruited from Amazon.com's Mechanical Turk platform. The results of Experiment 1 indicate that the use of a true self-presentation style leads to greater self-reported happiness for high self-esteem users compared to low self-esteem users. By contrast, the use of a strategic self-presentation style results in more self-reported happiness for both high- and low-self-esteem users. Following self-determination theory, which emphasizes the importance of feeling effective in one's environment, a mediation test was further conducted in Experiment 2, demonstrating that revealing a true self on Facebook effectively satisfies the high self-esteem user's need for competence, thus explaining greater degrees of self-reported happiness. Highlights: True self-presentation made high self-esteem FB users happy. Strategic self-presentation made both high and low self-esteem FB users happy. High self-esteem FB users felt greater degrees of vitality after engaging with FB.